Information War in Syria - N. A. Smirnov (Vestnik MGIMO-Universiteta)
In recent years, in many countries around the world the role of society in political decision making quickly strengthened, and the population is increasingly affects the position of the state leaders. For countries pretending to have the support of its policies in other regions, public diplomacy is an essential tool. Today, public diplomacy is regularly used in various conflicts, one of which is the civil war in Syria. Media, Internet, social networks and other tools are used daily to cover the events and create the necessary views of the population in different countries. At the beginning of the article the reasons for the outbreak of the war are discussed from the standpoints of the main actors - the current Syrian government and its opposition, as well as their allies and enemies. The causes of the conflict are essential for further evaluation of the evs, so diametrically opposite points of view of the main actors of the events are analyzed in the material. Then we consider the coverage of the war, because period of direct military action is important to assess the behavior of its members. Among the most important and controversial topics covered by the international media in the conflict, are the use of prohibited weapons, killing of civilians, a violation of international agreements. Determination of the prospects of civil war in Syria is also critical when planning further action by all these events. To get the necessary public support, the parties are trying to have different interpretation of further scenarios. Much depends on this: whether the country's population supports the direction of further assistance or troops, how residents of other countries would react to a further continuation of the conflict, or how the representatives of international organizations would answer the question about the legitimacy of any move. The formation of public opinion in different countries aimed at obtaining approval of its policy on the part of the population and the necessary support for further action. Each of the parties to the conflict, using its own and is making significant opportunities attempts to provide the necessary coverage of the events in this war. Analyzing numerous publications, photos and videos, largely specially rigged to achieve the desired result, it is difficult to say about the objective picture of what is happening, but it is an indisputable fact of enormous human sacrifices, millions of people who have fled their country and the destroyed country in the heart of the Middle East.